Bone-vessels relationships: association between calcifications of the iliac arteries with vertebral fractures in hemodialysis patients – results from the VIKI study. (14th October 2021) - Fusaro, M; Tripepi, G; Politi, C; Aghi, A; Taddei, F; Schileo, E; De Caterina, R
Abstract: Background: Vascular calcification and fragility fractures are common age-related disorders, associated with high morbidity and mortality especially in end-stage renal disease. Skeletal disorders occur in dialysis patients. Few studies have provided data on the prevalence of vertebral fractures (VF) and their association with large artery calcifications. Purpose: We evaluated the relationship of iliac arteries calcifications (IACs) and abdominal aorta calcifications (AACs) with the risk for VFs in hemodialysis (HD) patients. Methods: The VIKI Study is a cross-sectional study involving 387 HD patients from 18 Italian dialysis centers, assessing demographic, clinical and biochemical data in such patients. Biochemical data included bone health markers such as vitamin K levels, vitamin K-dependent proteins, vitamin 25(OH)D, alkaline phosphatase, parathormone, calcium, phosphate, Bone Gla Protein and Matrix Gla Protein. The presence of VF, IACs and AACs were determined through standardized radiograms of the spine. A >20% reduction of vertebral body height was considered a VF. We quantified vascular calcifications by measuring the length of calcium deposits along the abdominal arteries, classifying the degree of severity for the IACs and AACs with a specific score (mild: 0.1–3 cm; moderate: 3.1–5 cm; and severe >5 cm) previously validated for AACs. Results: The prevalence of IACs was 56.1%, and of AACs 80.6%. After adjusting for confounding variables, the presence of IACs was associated with 73% higher odds of VF (p=0.028), whereas we found no association (p=0.294) for AACs. The presence of IACs associated with VF irrespective of calcification severity. Patients with IACs had lower levels of the vitamin K2, menaquinone 7 (0.99 vs 1.15 ng/ml; p=0.003), and deficiency of this marker became greater when adjusting for triglyceride levels (0.57 vs 0.87 ng/ml; p<0.001). Conclusions: The presence of IACs, regardless of their extent, appears to be a clinically relevant risk factor for VFs. The association is further enhanced by including vitamin K, a main player in bone and vascular health, in the model. Prospective studies are needed to confirm these findings both in chronic kidney disease patients and in the general population. Funding Acknowledgement: Type of funding sources: None.